2014
DOI: 10.1111/acer.12331
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Disease Associated with Alcohol Use Disorders in the United States

Abstract: Background Alcohol use disorders (AUD) have long been considered to be some of the most disabling mental disorders; however, empirical data on the burden of disease associated with AUD have been sparse. The objective of this article is to quantify the burden of disease (in disability-adjusted life years [DALYs] lost), deaths, years of life lost due to premature mortality (YLL), and years of life lost due to disability (YLD) associated with AUD for the United States in 2005. Methods Statistical modeling was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 45 publications
3
147
0
8
Order By: Relevance
“…Alcohol dependence causes an extremely high burden on society, due to its consequences on health, on criminality and hazards to others. [3][4][5] However, a majority of alcoholic subjects do not even have access to therapy. 6 Hence, treating alcohol-dependent (AD) subjects is certainly an important challenge for the medical community, and a multidisciplinary approach could be promoted in order to integrate contributions from various fields of expertise, including psychological, social and biological approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dependence causes an extremely high burden on society, due to its consequences on health, on criminality and hazards to others. [3][4][5] However, a majority of alcoholic subjects do not even have access to therapy. 6 Hence, treating alcohol-dependent (AD) subjects is certainly an important challenge for the medical community, and a multidisciplinary approach could be promoted in order to integrate contributions from various fields of expertise, including psychological, social and biological approaches.…”
Section: Introductionmentioning
confidence: 99%
“…As example of individual damages, there is the exacerbating or contributing to a multitude of health and social problems, including physical and psychological illness; interpersonal conflicts; violence and legal problems; unemployment; poverty; deleterious reproductive outcomes; disability; and premature death [9]. This was ratified by , who found that Alcohol Use Disorders (AUD) were shown to be responsible for a sizable portion of mortality and the burden of disease in the United States, a finding similar to recent European studies with slightly different methodology [10,11,49].…”
Section: Introductionmentioning
confidence: 65%
“…Alcohol consumption has negative effects on society because of alcohol-related mortality and morbidity [48], decreasing users' health and related people's safety and comfort. For example, the numbers of deaths associated with AUD were considerable: we estimated that approximately 53, 000 male deaths and 12, 000 female deaths in the United States in 2005 were associated with AUD [49]. In France, out of 535000 deaths in 2009, 49000 were attributable to alcohol: 36500 among men and 12500 among women, which represent 13 and 5%, respectively, of total deaths [50].…”
Section: Socioeconomics Impacts Of Use Of Alcoholmentioning
confidence: 97%
See 2 more Smart Citations